Correlations between oil and stock markets: a wavelet-based approach - Martín-Barragan, B.; Ramos, S.; Veiga, H. (Economic Modelling, 2015)
In a global economy, shocks occurring in one market can spill over to other markets. This paper investigates the impact of oil shocks and stock market crashes on correlations between stock and oil markets. We test changes in correlations for different time scales with non-overlapping confidence intervals based on estimated wavelet correlations. Our results indicate that correlation between oil and stock markets tends to be stable in non-shock periods, around zero, but this changes during oil and financial shocks both at higher and lower frequencies. We find evidence of contagion, in particular during the 2008 and 2011 stock market falls. At low frequencies, the number of correlation breakdowns during oil shocks and stock market crashes is higher and they can be interpreted as shifts in market co-movements.